Establishing and streamlining the communication and coordination through emergency control room in a tertiary care hospital by upgrading the available resources in the pandemic of COVID-19 - Chugh, Latika T.; Chawada, Bansari L.; Patel, Sangita V. (International Journal Of Community Medicine And Public Health, 2024)
As the COVID-19 pandemic started, a tertiary care hospital of central Gujarat faced problems in developing communication and coordination between the doctors as there was a lack of emergency control room (ECR) set up. This article documents the process of establishing ECR using locally available resources. The department of Community Medicine (CM) was made in-charge of ECR. All information technology (IT) equipment were supplied by hospital administration as per the demand. Various challenges experienced by the staff of CM were discussed with the authorities and specialists from respective departments and quick intermediate solutions were adopted. In July-2020, ECR was established with IT support which accelerated the sharing of laboratory findings and patient details to the treating physician. Dedicated smart phones were assigned to each floor providing real time patient updates through Whatsapp groups and video calling feature was used to establish effective communication between patients and relatives. The hospital also collaborated with a local NGO that provided manpower to address queries at ECR. This study concludes that focusing on utilising local resources and manpower and training the available personnel to handle the problems in the best possible ways made the system work properly at the time of crisis.